Biochemical characterization of the endo-α-N-acetylgalactosaminidase pool of the human gut symbiont Tyzzerella nexilis. (April 2020) - Kulinich, Anna; Wang, Qian; Duan, Xu-Chu; Lyu, Yong-Mei; Zhang, Xiao-Yang; Awad, Faisal Nureldin; Liu, Li; Voglmeir, Josef
Abstract: Three large (2084-, 984-, and 2104-amino acids) endo-α-N-acetylgalactosaminidase candidate genes from the commensal human gut bacterium Tyzzerella nexilis were successfully cloned and subsequently expressed in Escherichia coli . Activity tests of the purified proteins revealed that two of the candidate genes (Tn0153 and Tn2105) were able to hydrolyze the disaccharide unit from Galβ1-3GalNAc-α- p NP. The biochemical characterization revealed optimum pH conditions of 4.0 for both enzymes and temperature optima of 50 °C. The addition of 2-mercaptoethanol, Triton X-100 and urea had only minor effects on the activity of the enzymes, and the addition of imidazole and sodium dodecyl sulfate led to a significant reduction of the enzymes' activities. A mutational study identified and confirmed the role of the catalytically significant amino acids. The present study describes the first functional characterization of members of the GH101 family from this human gut symbiont. Graphical abstract: Image 1